2009
DOI: 10.1038/modpathol.2009.105
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical differential diagnosis between thymic carcinoma and type B3 thymoma: diagnostic utility of hypoxic marker, GLUT-1, in thymic epithelial neoplasms

Abstract: There are only a few immunohistochemical markers that are useful for differentiating thymic carcinomas from type B3 thymomas. The purpose of this study is to examine the additional markers that would be useful for differentiating between thymic carcinoma and thymoma type B3. We performed a tissue microarray analysis of surgically resected thymic tumor specimens from12 cases of thymic carcinoma, 7 cases of type B3 thymoma, and 68 cases of other types of thymoma. Immunostaining using 49 antibodies was scored bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 32 publications
(39 reference statements)
2
64
0
Order By: Relevance
“…119,122 Interestingly, most of the thymic carcinomas have been positive for p63 and PAX8. 121,122,124 Classification of thymic NETs is similar to that of pulmonary NETs, including TC, AC, LCNEC, and small cell carcinoma. The diagnostic morphologic criteria of thymic NETs are similar to those of their counterparts in the lung.…”
Section: Application Of Ihc For the Differential Diagnosis Of Sarcomamentioning
confidence: 99%
See 1 more Smart Citation
“…119,122 Interestingly, most of the thymic carcinomas have been positive for p63 and PAX8. 121,122,124 Classification of thymic NETs is similar to that of pulmonary NETs, including TC, AC, LCNEC, and small cell carcinoma. The diagnostic morphologic criteria of thymic NETs are similar to those of their counterparts in the lung.…”
Section: Application Of Ihc For the Differential Diagnosis Of Sarcomamentioning
confidence: 99%
“…SPT24 shows greater sensitivity in detecting more pulmonary tumors of all histologic subtypes at the expense of its specificity, contributing to a few reported expressions of TTF1 in breast, colon, and gynecologic tumors and colon. [123][124][125][126][127][128][129][130][131][132] Thus, 8G7G3/1 might be a better choice to differentiate primary from metastatic carcinomas. In recent years, many organspecific markers have been established.…”
Section: Application Of Ihc For the Differential Diagnosis Of Sarcomamentioning
confidence: 99%
“…(online first, page number not for citation purpose) crease in the expression of glucose transporter in lung cancer and thymic epithelial tumors [18,29] . A higher expression of SGLT1 has also been found in ovarian, colorectal, and lung cancer tissues compared to healthy tissues, indicating a positive correlation between the activity of glucose transporters and tumor development [30] .…”
Section: Expression Of Glucose Transporters In Tumor Cellsmentioning
confidence: 99%
“…Willis et al [29] compared two diagnostic pathways: TRUS-guided biopsy against multiparametric MRI (mpMRI), followed by MRI-targeted biopsy, if positive. The study suggested that mpMRI and consequent MRI-targeted biopsy might result in biopsies that are more accurate and fewer in number as compared with TRUS-guided biopsies.…”
Section: Sensitivity and Specificity In The Detection Of Prostate Canmentioning
confidence: 99%
“…Some studies have shown that there is a significant in- crease in the expression of glucose transporter in lung cancer and thymic epithelial tumors [18,29] . A higher expression of SGLT1 has also been found in ovarian, colorectal, and lung cancer tissues compared to healthy tissues, indicating a positive correlation between the activity of glucose transporters and tumor development [30] .…”
Section: Expression Of Glucose Transporters In Tumor Cellsmentioning
confidence: 99%